Factors Affecting The Value of Companies in the Mining Sector - Feny Fidyah; Afrila Eki Pradita (Green Publisher Indonesia, 2022)
Losses due to the Covid-19 pandemic have a global impact on the life of a country, including companies in all sectors. Mining sector companies listed on the Sharia Securities List are also affected by this pandemic and are demanding companies to work harder for better productivity and selling points than the previous year. This study aims to determine factors such as company characteristics (ROA, DER, CR and size) that affect the mining sector company value (PBV) on the Sharia Securities List listed on the Indonesia Stock Exchange (IDX). The data used is secondary data obtained from the website www.idx.co.id. The research period starts from 2015 – 2020. The samples obtained were using non-probability sampling with purposive sampling method and the samples obtained were 8 companies. Multiple linear regression analysis and hypothesis testing are analytical techniques used. The result of this research is ROA has an effect on PBV. DER, CR and size partially have no effect on PBV. Mining sector companies listed on sharia securities should pay attention to company characteristics such as DER, CR and size to increase company value.